Alfalfa modified the effects of degraded black soil cultivated land on the soil microbial community - Mei, Linlin; Zhang, Na; Wei, Qianhao; Cao, Yuqi; Li, Dandan; Cui, Guowen (Frontiers in Plant Science, 2022)
Legume alfalfa (Medicago sativa L.) is extensively planted to reduce chemical fertilizer input to the soil and remedy damaged fields. The soil mechanism of these effects is potentially related to the variations in alfalfa-mediated interactions of the soil microbial community. To understand the impact of planting alfalfa on the soil microbial community in degraded black soil cultivated land, a 4-year experiment was conducted in degraded black soil cultivated land. We assessed soil parameters and characterized the functional and compositional diversity of the microbial community by amplicon sequencing that targeted the 16S rDNA gene of bacteria and ITS of fungi in four systems under corn cultivation at the Harbin corn demonstration base (Heilongjiang, China): multiyear corn planting (more than 30 years, MC1); 2 years of alfalfa-corn rotation (OC); 3 years of alfalfa planting (TA); and 4 years of alfalfa planting (FA). It was found out that alfalfa led to changes in the alpha diversity of soil bacteria rather than in fungi in the degraded arable land. The abundance of the bacterial groups Gemmatimonadetes, Actinobacteria, Planctomycetes, and Chloroflexi was increased in OC, while Proteobacteria and Acidobacteria and the fungal group Glomeromycota were increased in TA and FA. OC, TA, and FA significantly increased the pH level but reduced soil electrical conductivity, but they had no impact on soil available nitrogen and soil available potassium at the 0–15 cm soil depth. However, with the years of alfalfa planting, soil available nitrogen and soil available potassium were reduced at the 15–30 cm soil depth. OC, TA, and FA significantly reduced the soil available phosphorus and soil total phosphorus at the 15–30 cm soil depth. There was no significant impact made on soil total nitrogen. FA significantly reduced the soil organic matter at the 15–30 cm soil depth. Planting alfalfa in degraded black soil cultivated land can reduce the salt content of the soil, and the nutrient content of soil planted with alfalfa without fertilization was equivalent to that of degraded corn cultivated land with annual fertilization. Besides, alfalfa recruited and increased contained taxa with the capacity to improve soil nutrient utilization and inhibit the harmful influences of pathogens for subsequent crops. Meanwhile, the planting of alfalfa can modify soil conditions by promoting the proliferation of specific beneficial microbiota groups.